Construction and Evaluation of Recombinant Chimeric Fibrillin and Elastin Fragment in Human Mesenchymal Stem Cells - Jeong, Eui-Seung; Park, Bo-Hyun; Lee, Sujin; Jang, Jun-Hyeog (Protein and Peptide Letters, 2022)
Background: Diverse extracellular matrix (ECM) proteins physically interact with stem cells and regulate stem cell function. However, the large molecular weight of the natural ECM renders large-scale fabrication of a similar functional structure challenging. Objective: The objective of this study was to construct a low molecular weight and multifunctional chimeric form of recombinant ECM to stimulate mesenchymal stem cell (MSC) for tissue repair. We engineered Fibrillin-1PF14 fused to an elastin-like polypeptide to develop a new biomimetic ECM for stem cell differentiation and investigated whether this recombinant chimeric Fibrillin-Elastin fragment (rcFE) was effective on human nasal inferior turbinate-derived mesenchymal stem cells (hTMSCs). Methods: hTMSCs were grown in the medium supplemented with rcFE, then the effect of the protein was confirmed through cell adhesion assay, proliferation assay, and real-time PCR. Results: rcFE enhanced the adhesion activity of hTMSCs by 2.7-fold at the optimal concentration, and the proliferation activity was 2.6-fold higher than that of the control group (non-treatment rcFE). In addition, when smooth muscle cell differentiation markers were identified by real-time PCR, Calponin increased about 6-fold, α-actin about 9-fold, and MYH11 about 10-fold compared to the control group. Conclusion: Chimeric rcFE enhanced cellular functions such as cell adhesion, proliferation, and smooth muscle differentiation of hTMSCs, suggesting that the rcFE can facilitate the induction of tissue regeneration.
Keywords: Extracellular matrix